Analysis of generalized frequency division multiplexing modulation - Blanco-Orta, Jorge Luis (2023)
In this article, an investigation is made of the Generalized Frequency Division Multiplexing (GFDM) modulation and its influence to improve the structure of the physical layer, taking into account the inherent advantages it presents for the development of new technologies. A comparison is made with Orthogonal Frequency Division Multiplexing (OFDM) modulation, used in the fourth generation (4G) mobile communication. Defining the characteristics that differentiate each of the signals, as well as the benefits for the network architecture, the enabling technologies and for being a modulation that can solve problems in massive multiple input multiple output (MIMO) systems. The research is carried out with the purpose of achieving greater data transmission, as this is a key technology that will face similar problems in future systems and improve the flexibility of the sixth generation (6G).